Rotavirus diarrhea is caused by nonreplicating viral particles. - Shaw, R D (1995)
Rotaviruses infect the villous epithelium of the small intestine and cause severe diarrhea in young children. The mechanism by which rotavirus causes diarrhea has not been elucidated. It has been hypothesized that rotavirus replication in the intestinal epithelium causes a loss of viable absorptive cells, leading to an imbalance of intestinal secretion and absorption. Cell destruction has generally been thought to result from rotavirus transcription and replication. However, the widely used heterologous murine model of rotavirus infection demonstrates minimal viral replication and histological changes limited to epithelial vacuolation on the distal villus despite the simultaneous occurrence of voluminous liquid diarrhea. We have genetically inactivated rotaviruses to test the importance of viral replication in the pathogenesis of rotavirus-induced diarrhea. We present direct evidence that transcription- and replication-defective rotaviruses cause diarrhea in an animal model. These findings suggest that rotavirus attachment or entry into cells is sufficient for the induction of diarrhea. The mechanism of rotavirus-induced diarrhea is therefore consistent with a viral toxin-like effect exerted during virus-cell contact.